Hyaluronan Does Not Affect Bupivacaine’s Inhibitory Action on Voltage-Gated Potassium Channel Activities in Bovine Articular Chondrocytes - William Hester; Jinnan Yang; Guo-Yong Wang; Sen Liu; Michael J. O'Brien; Felix H. Savoie; Zongbing You (Advances in Orthopedics, 2012)
Objectives. The objective of this paper is to determine if hyaluronan affects bupivacaine’s anesthetic function. Methods. Whole cell patch clamp recordings were performed on bovine articular chondrocytes cultured in 60 mm dishes. The chondrocytes were treated with phosphate-buffered saline (control group), 7.5 mg/mL hyaluronan (Orthovisc), 0.25% bupivacaine, or a mixture of 7.5 mg/mL hyaluronan and 0.25% bupivacaine. Outward currents were elicited by step depolarization from −90 mV to 150 mV with 5 mV increments and holding for 200 ms. Results. The amplitude of outward currents elicited at 150 mV was 607.1±135.4 pA (mean ± standard error) in the chondrocytes treated with phosphate buffered saline, 550.0±194.9 pA in the chondrocytes treated with hyaluronan, 18.4±8.3 pA in the chondrocytes treated with bupivacaine, and 12.8±2.6 pA in the chondrocytes treated with a mixture of hyaluronan and bupivacaine. Conclusion. Hyaluronan does not affect bupivacaine’s inhibitory action on the potassium channel activities in bovine articular chondrocytes. This finding suggests that intra-articular injection of a mixture of hyaluronan and bupivacaine may not affect the anesthetic effects of bupivacaine.